Number Sense in Siblings of Children with Mathematical Learning Disabilities: A Longitudinal Study (Journal of Intellectual Disability - Diagnosis and Treatment, 2013)
Number sense, counting and logical thinking were assessed in 14 siblings of children with Mathematical Learning Disabilities (MLD) and in 41 age matched children without family members with MLD. The children were tested in kindergarten and followed up in grade 1. A 0-100 number line estimation paradigm with three formats (Arabic digits, dots and number) was used as a measure of number sense. Results reveal that siblings of children with MLD are less proficient in number line placements compared to non-siblings, with both groups having a logarithmic representation in kindergarten and grade 1. Siblings also differ from non siblings on procedural and conceptual counting knowledge and logical thinking in kindergarten. In addition, our findings suggest that nnumber line estimation in kindergarten is especially predictive for untimed procedural calculation performances in grade 1, whereas procedural counting knowledge is related to timed fact retrieval skills in grade 1. Our findings also reveal that MLD had a familial aggregation. Clinical siblings especially differ from non-clinical siblings on the estimation with Arabic numbers (in kindergarten and grade 1) and number words (in grade 1), pointing to the fact that especially symbolic number line estimation tasks on a 0-100 scale can be used as screeners for MLD. Implications for the understanding and diagnosis of MLD are discussed.